2014
DOI: 10.3174/ajnr.a3923
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging Features and Predictors of Outcome in Eclamptic Encephalopathy: A Prospective Observational Study

Abstract: BACKGROUND AND PURPOSE:Posterior reversible encephalopathy syndrome is associated with eclampsia. We assessed the distribution and nature of typical and atypical cranial MR imaging findings in these patients and their correlation with clinical and laboratory data and predictors of outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 23 publications
2
34
1
Order By: Relevance
“…Many previous studies, observed hemorrhagic lesions in 9-33% cases of PRES on neuroimaging. 2,7,24,25 In the present study 3 (9.9%) patients with PRES had hemorrhagic complications. This finding is in consistent with study done Moyama et al 6 …”
Section: Figure 1: Persistent Symptomsmentioning
confidence: 85%
See 3 more Smart Citations
“…Many previous studies, observed hemorrhagic lesions in 9-33% cases of PRES on neuroimaging. 2,7,24,25 In the present study 3 (9.9%) patients with PRES had hemorrhagic complications. This finding is in consistent with study done Moyama et al 6 …”
Section: Figure 1: Persistent Symptomsmentioning
confidence: 85%
“…7 Few studies have reported enhanced maternal deaths in eclampsia associated with PRES. The outcome of pregnant women with PRES was usually reported as favorable, with resolution being rapid and complete after adequate therapy, although permanent damage can persist, and death due to hemorrhage was described.…”
Section: Figure 2a 2b 2c and 2d: Mri Images Of One Of The Patients mentioning
confidence: 99%
See 2 more Smart Citations
“…Hence their elevation just suggests diffuse endothelial dysfunction, and absolute values may not correlate with the degree of cerebral endothelial dysfunction and hence with severity of cerebral edema or, for that matter, the extent of edema. 3 Therefore, more studies are required not only warranting the exact relationship of serum LDH with severity of cerebral edema in PRES, but also trying to identify specific biomarkers of cerebral vascular endothelium and establishing its relationship with the severity of PRES.…”
mentioning
confidence: 99%